2016
DOI: 10.1111/jbfa.12199
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Regulations on Pension Risk Shifting: Evidence from the US and Europe

Abstract: This paper provides evidence that pension regulations can incentivize or curb risk shifting in the investment of defined benefit (DB) plan assets. We document that in the U.S., whereby the pension insurance premium charged by the Pension Benefit Guaranty Corporation (PBGC) is largely flat, financially distressed firms with severely underfunded plans shift pension investment risk. We further find that risk shifting is mitigated in the U.K. after the implementation of risk-adjusted pension insurance premium, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 66 publications
1
11
0
1
Order By: Relevance
“…While distressed firms decrease risk-taking in investments, firms with underfunded plans increase risk-taking; further, increased risk-taking occurs when firms are both distressed and underfunded. Guan and Lui (2016) also found similar results. Using data from the UK, Cocco and Volpin (2007) found that sponsors with underfunded plans and many insider trustees, that is, those trustees who are also executive directors of the sponsor, tend to increase risk-taking.…”
Section: Literature Reviewsupporting
confidence: 68%
See 1 more Smart Citation
“…While distressed firms decrease risk-taking in investments, firms with underfunded plans increase risk-taking; further, increased risk-taking occurs when firms are both distressed and underfunded. Guan and Lui (2016) also found similar results. Using data from the UK, Cocco and Volpin (2007) found that sponsors with underfunded plans and many insider trustees, that is, those trustees who are also executive directors of the sponsor, tend to increase risk-taking.…”
Section: Literature Reviewsupporting
confidence: 68%
“…Although the premium increases in line with the level of underfunding of the pension fund, it is largely flat with respect to risk-taking. Guan and Lui (2016) found that risk-shifting is mitigated in the UK, where pension insurance premiums depend on risk-taking, as well as in the Netherlands, where full pension funding is mandatory. Love et al (2011) showed that risk-shifting is the optimal investment strategy when the pension insurance premium is not pre-adjusted to the fair price in terms of risk-taking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pension assumptions affect the estimated value of pension liabilities and thus contribution requirements. Furthermore, managers have considerable control over the allocation of pension plan assets (Guan and Lui, ). Managers have better information about how pension liabilities are likely to evolve in the future.…”
Section: Background Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…For example, Kabir et al. () study the effect of the pension component of executive compensation on the cost of debt, and Goh and Li () examine whether the pay‐performance sensitivity increases as the pension component of the executive component increases.…”
mentioning
confidence: 99%
“…However, research has highlighted the flexibility management has in the contribution decision, suggesting these mechanisms may not be binding (Chaudhry et al., ). Therefore, our analyses add to the literature that speaks to the effectiveness of these mechanisms put in place by regulators and the PBGC (Guan & Lui, ).…”
Section: Introductionmentioning
confidence: 96%